A secularização e sua influência na constituição e na dinâmica da família católica pós-moderna em Vitória de Santo Antão (PE), Brasil - Lima, Luciano da Silva (2016)
The media and the Brazilian Institute of Geography and Statistics (IBGE, 2010) have conveyed the changes that have taken place both in the structure as in the dynamics of post-modern family in Brazil and in the world in recent decades. There are so many new types of family: single parent, multiple, two people coreless, homosexual, with ghost, among many others. This work of the Masters in Religious Studies has as General Purpose to identify and critically analyze the positive and negative aspects of secularization influencing the formation and dynamics of postmodern Catholic family in Vitoria de Santo Antão (PE), Brazil. The methodology consisted of a literature, descriptive, cross-sectional, with the use of a research of field, having as main theorists J. Comblin, Peter Berger, Pierpaolo Donati, J. Carlos Petrini and Felipe Aquino. As instrument was used a questionnaire composed of 12 questions, applied to a convenience sample of 20 couples of St. Anthony Parish, being 10 couples of 1-5 years of married life and 10 couples with more than 20 years of marriage. It was used the percentage in quantitative analysis, and other media tools that can help us achieve the General Objective of the dissertation and the specific ones: a) to evaluate the power of secularization and its influence on the dynamics of contemporary Catholic family in Vitoria de Santo Antão (PE); b) to contextualize the constituent factors of the Catholic family in a secularized world, and c) to address the postmodern thought in relation to the Catholic family in the Catholic perspective of the Sacrament of Marriage that was very positive in this work.